2016
DOI: 10.1093/pch/21.4.191
|View full text |Cite
|
Sign up to set email alerts
|

Thanks for asking: Adolescent attitudes and preferences regarding the use of chaperones during physical examinations

Abstract: Although there was variation in adolescents' attitudes and preferences regarding the use of chaperones, many females indicated a desire to discuss the option of a chaperone for all types of examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Prior research evaluating patient preferences suggest that females are generally more inclined to prefer chaperones as compared with their male counterparts. 7,13,[20][21][22][23][24][25] However, as many as 38% of male respondents in these studies do in fact desire a chaperone. 7,13,21,24,25 Although difficult to assess, it is likely that sex identification and sexual orientation play a significant role in many of these trends, both in terms of provider practices as well as patient preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research evaluating patient preferences suggest that females are generally more inclined to prefer chaperones as compared with their male counterparts. 7,13,[20][21][22][23][24][25] However, as many as 38% of male respondents in these studies do in fact desire a chaperone. 7,13,21,24,25 Although difficult to assess, it is likely that sex identification and sexual orientation play a significant role in many of these trends, both in terms of provider practices as well as patient preferences.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 1986 in the USA suggested that few adolescents would want to have a chaperone present for pelvic examination15 and Feldman et al 10 found most (99.6%) adolescent patients and/or their families declined the offer of a chaperone, although no explanation for the role of the chaperone was given to the patients. More recent data from Canada showed that 61% of adolescents wanted the choice of a chaperone for an intimate examination, with only 29% reporting that they would not want a chaperone present at all 4. Qualitative studies report some patients feel more embarrassed by the presence of a chaperone, whereas for other patients a chaperone made them feel more at ease 4 11.…”
Section: Discussionmentioning
confidence: 99%
“…More recent data from Canada showed that 61% of adolescents wanted the choice of a chaperone for an intimate examination, with only 29% reporting that they would not want a chaperone present at all 4. Qualitative studies report some patients feel more embarrassed by the presence of a chaperone, whereas for other patients a chaperone made them feel more at ease 4 11. Considering this, many of these studies advocate the importance of patient choice 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The access to such assistance seems particularly valuable for minor patients, and the research conducted in Canada included both medical staff and family members in this role. According to the surveyed girls, a chaperone guarantees additional safety (65%), provides emotional (63%) and informative (55%) support, and can even speak up for patients (44%) [19].…”
Section: Sense Of Uneasiness Related To a Gynaecologist Appointmentmentioning
confidence: 99%